PERANAN CORPORATE GOVERNANCE DALAM MENGURANGI KECURANGAN LAPORAN KEUANGAN - Arief Mulyadianto, (2020)
This research was conducted with the aim to test and find out the role of corporate governance in reducing financial statement fraud. The variables used in this study are the performance of the board of commissioners, audit committee financial expertise, and institutional ownership as an independent variable and for the dependent variable using fraudulance financial statements with the Beneish M-Score proxy. The sample used in this study is manufacturing companies listed on the Indonesia Stock Exchange. The analysis technique used uses SPSS with a significance level of 5%. The results of this study are the performance of the board of commissioners, audit committee financial expertise and institutional ownership has no effect in reducing fraudulance financial statements.